Determination of Inorganic Anions in Eucheuma cottonii and Carrageenan by Suppressed Ion Chromatography - Suhaili, Refilda; Munaf, Edison; Zein, Rahmiana; Sedyohutomo, Anang; Wah Lim, Lee; Takeuchi, Toyohide (Asian Journal of Chemistry, 2011)
Inorganic anions in Eucheuma cottonii (a species of red algae) and carrageenan were determined by ion chromatography with a packed-column suppressor system. Two packed-column suppressors were connected in series via a 10-port switching valve for continuous chromatographic runs. Sodium carbonate-bicarbonate solution was used as the mobile phase and its background conductivity was reduced significantly by the suppressor, leading to achievement of lower detection limits. F–, Cl–, Br–, NO3–, HPO42-, SO42- and I– contained in Eucheuma cottonii and carrageenan were determined within 15 min. The detection limits obtained by the present method were 2.7-12 nM for these anions.